The association between bullying victimization and suicidal ideation among students in Africa: a systematic review and meta-analysis - Bezie, Anmut Endalkachew; Yohannes, Lamrot; Yirdaw, Asmare Asrat; Sergindo, Mihretu Tagesse; Begena, Biniam Belete; keleb, Awoke (Frontiers in Public Health, 2025)
IntroductionBullying victimization through cyberbullying, verbal threats, insults, or nicknames, and physically, like stealing or exclusion from the peer group, is a significant challenge for schools and teachers in educational settings. It is a precursor for suicidal ideation and has an adverse effect on students’ mental health. Therefore, we performed a systematic review and meta-analysis to investigate the association between bullying victimization and suicidal ideation among students in Africa.MethodsA thorough search of literature was conducted through international electronic databases to identify relevant studies on the association between bullying victimization and suicidal ideation. Studies published up to October, 2024 were included. The recommended PRISMA guideline was used for reporting items for this systematic review and meta-analysis. To extract and analyze data, Microsoft Excel 16 and STATA 17 software were used, respectively. The quality of the included studies was examined using the Joanna Briggs Institute critical appraisal checklist. The funnel plot and Egger’s regression test were applied to evaluate publication bias. To estimate the pooled association and heterogeneity, a random effects model and I2 test statistics were used, respectively.ResultsThis study included 16 articles that met the inclusion criteria, encompassing a total sample size of 34,007. Students with bullying victimization were 1.7-fold more prone to suicidal ideation than their counterparts (OR = 1.68, 95% CI: 1.56–1.81, I2 = 60.9%, p < 0.001). Subgroup analyses demonstrate that moderate but slightly higher heterogeneity was found among secondary school students than tertiary students and moderate heterogeneity but a high odds ratio among tertiary students. In addition, higher heterogeneity was found from primary studies than that of studies using secondary data analysis. Sensitivity analyses confirmed the robustness of these findings.ConclusionThe findings of this study demonstrated that students with bullying victimization were at higher risk of suicidal ideation than their counterparts who were not victimized. Therefore, interventions focused at school-based anti-bullying programs, counseling services, parental involvement, and improving social and peer supports were advised to mitigate the effect of bullying and reduce suicidal ideation.Systematic Review Registrationhttps://www.crd.york.ac.uk/PROSPERO/view/CRD42024615422